Incorporating the HPLC-ESI-Q-TOF-MS profiles with the biochemical properties of eight Salvia species - Llorent-Martinez, Eulogio J.; Nilofar, Kouadio Ibrahime; Sinan, Kouadio Ibrahime; Darendelioglu, Ekrem; Bahsi, Muammer; Polat, Ridvan; Zengin, Gokhan (Wiley, 2025)
Salvia, a widely recognized genus globally esteemed for its traditional and medicinal applications, prompted our investigation into the methanol and water extracts of eight Salvia species native to Turkey. These species included S. aucheri, S. candidissima, S. divaricata, S. virgata, S. multicaulis, S. palestina, S. trichoclada, and S. cerino-pruinosa. Our study aimed to assess their biological properties and chemical composition. Utilizing HPLC-ESI-Q-TOF-MS, we identified chemical constituents in the extracts, while antioxidant (radical quenching, reducing power, and metal chelating) and enzyme inhibitory (amylase, glucosidase, tyrosinase, and cholinesterase) activities were evaluated for biological activities. One hundred thirty-one compounds were characterized in the tested extracts. Although many compounds belonging to different chemical families were identified, the main compounds in all the extracts were rosmarinic and sagerinic acids, along with several salvianolic acid isomers. Notably, the methanol extracts displayed superior antioxidant properties overall, with S. cerino-pruinosa exhibiting the highest activity among them, except for metal chelating. Similar to the antioxidant test results, the methanol extracts were more active than the water extracts in the enzyme inhibition tests. Multivariate analysis further highlighted the distinctiveness of the water extract of S. cerino-pruinosa. In conclusion, our findings underscore the biopharmaceutical potential of the tested Salvia species, suggesting their significance as sources of bioactive agents for health-promoting applications.
Keywords: biopotential; data analysis; health-promoting agents; rosmarinic acid; Salvia